Increasing Emotional Engagement in Anticipating Bullying and Strengthening Children's Creativity through Expressive Innovation Mediums - I Nyoman Larry Julianto; Ida Bagus Hari Kayana Putra; Ni Luh Sustiawati; Ni Luh Indah Desira Swandi; Ni Putu Elvian Andreani (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2026)
The increasing number of bullying cases in Indonesian educational environments has a serious impact on children's emotional, social, and creative development. This condition demands interventions that are not only curative but also preventative, by strengthening emotional bonds between children, peers, teachers, and parents. The Nusantara Arts Innovation Program (PISN), implemented in collaboration with the Kupu-Kupu Learning Center in Sidan, Gianyar, Bali, designed the Expressive Innovation Medium (MIE) as a collaborative arts approach that integrates art, design, and psychology to strengthen emotional engagement while encouraging creativity. The main activities included screenings of educational anti-bullying animations and a series of art activities: tie-dye, ecoprinting with natural dyes, paper waste processing, and painting on t-shirts with Balinese art and culture themes that are close to children's daily lives. This community service research used a descriptive qualitative approach through participatory observation, brief interviews with teachers and administrators, and documentation of the work and activity processes that were analyzed thematically. The results showed increased active participation, children's courage to express their opinions, the emergence of spontaneous discussions about bullying, and a warmer, more collaborative, and more supportive learning atmosphere. The resulting works showcased diverse and original explorations of color, shape, and local cultural motifs. Teachers and administrators considered MIE relevant as a medium for dialogue about empathy, diversity, and how to respond constructively to bullying. These findings strengthen the evidence that arts-based interventions and social-emotional learning can be effective preventative strategies to reduce the risk of bullying while fostering creativity, self-confidence, and social connectedness in children in non-formal education settings. Furthermore, the program has produced a model of good practice with the potential to be replicated in other educational institutions through the development of modules, thematic animations, and collaborative arts activity guides.